Pediatric keratoconus: a review of the literature - Mukhtar, Sabrina; Ambati, Balamurali K. (International ophthalmology, 2018)
Purpose To describe the epidemiology and prevalence, rates of progression, difference between adult and pediatric populations, and therapeutic approaches to pediatric keratoconus from documented literature. Methods A literature search was done on PubMed using key words including pediatric keratoconus, children with keratoconus, adult keratoconus, penetrating keratoplasty, corneal cross-linking and intracorneal ring segments. The literature was reviewed and reported to explore the key epidemiological differences between the pediatric and adult population with regards to presentation and treatment options. Results Pediatric keratoconus is more aggressive than adult keratoconus, which has been explained by structural differences in the cornea between both populations. High rates of progression were documented in pediatric populations. While corneal collagen cross-linking, intracorneal ring segments and penetrating keratoplasties have been used as therapies in the pediatric population, the literature overwhelmingly shows higher rates of failure and progression despite these measures as compared to adults. Conclusion Pediatric keratoconus is more aggressive than adult keratoconus, and current therapies used in adults may not be sufficient for the pediatric population.